Narrating Teacher Identity Across Generations in Rural Indonesia: Intersections of Professional, Moral, and Digital Resilience - I G A Widari; Iwan Jazadi (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2025)
This study explores how teacher identity is constructed and negotiated across generations in rural Indonesia through narrative inquiry and ethnographic engagement. Drawing on the stories of twelve senior teachers and twelve student teachers, the research reveals how professional identity is deeply rooted in moral values of pengabdian and community service, while continually redefined through changing educational contexts. The findings show that teaching remains a moral and relational vocation, yet increasingly mediated by technological adaptation and digital collaboration. Senior teachers exhibit digital resilience as they learn to integrate technology into pedagogical practices, while younger teachers demonstrate emerging forms of digital professional identity shaped by the use of online platforms, social media, and learning technologies. Generational differences in digital literacy and technological confidence highlight how identity formation now extends into digital spaces, where professional ethics meet technological innovation. By situating these narratives within the Technological Pedagogical Content Knowledge framework, the study identifies how cross-generational mentoring enables mutual learning—senior teachers offering pedagogical and moral guidance, and student teachers sharing digital expertise. This reciprocal dynamic forms a contextual TPACK model rooted in rural cultural realities. The study concludes that teacher identity is being reconstructed through intergenerational dialogue and digital transformation, offering new insights into professional development and policy design for rural teacher education.